2020
DOI: 10.1155/2020/8867183
|View full text |Cite
|
Sign up to set email alerts
|

ANCA-Associated Intrahepatic Duct Injury Associated with Levamisole-Adulterated Cocaine

Abstract: Damage to the liver or kidney can occur through direct toxic effects; however, damage can also be drug-induced immune-mediated. Levamisole-adulterated cocaine (LAC) is known to cause antineutrophil cytoplasmic antibody- (ANCA-) associated vasculitis and glomerulonephritis leading to acute kidney injury and end-stage renal disease. It remains unclear whether LAC is associated with hepatic duct damage. Here, we report a case with biopsy-proven evidence of intrahepatic duct damage months after being diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
4
1
Order By: Relevance
“…However, the biochemical changes seen with each drug treatment do not indicate liver damage. These results differ from a recent report of a levamisole‐adulterated cocaine user that presented hepatic damage 47 . Also, an analysis in lambs reported that a levamisole dose (20 mg/kg) similar to the one used in this study (17.7 mg/kg, i.p.)…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the biochemical changes seen with each drug treatment do not indicate liver damage. These results differ from a recent report of a levamisole‐adulterated cocaine user that presented hepatic damage 47 . Also, an analysis in lambs reported that a levamisole dose (20 mg/kg) similar to the one used in this study (17.7 mg/kg, i.p.)…”
Section: Discussioncontrasting
confidence: 99%
“…These results differ from a recent report of a levamisole-adulterated cocaine user that presented hepatic damage. 47 Also, an analysis in lambs reported that a levamisole dose (20 mg/kg) similar to the one used in this study (17.7 mg/kg, i.p.) increased liver enzymes.…”
Section: Discussionmentioning
confidence: 56%
“…Suspected substances were levamisole ( n = 10), methaqualone and several benzodiazepines, caffeine and acetaminophen ( n = 1), 5F-MDMB- PINACA ( n = 7) and phenethylamine ( n = 1), asbestos ( n = 1) [ 33 , 42 , 44 , 45 , 46 , 47 , 52 , 53 , 54 , 55 , 56 ]. Considering all of the reported cases, levamisole was the most prevalent adulterating agent in street cocaine ( n = 17 cases) [ 33 , 42 , 44 , 45 , 46 , 47 , 54 , 57 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Generally, ANCA positivity is a marker of autoimmune pathologies including systemic autoimmune vasculitis, necrotising crescentic glomerulonephritis, inflammatory bowel disease and other autoimmune pathologies [ 63 ]. In levamisole-adulterated cocaine intoxications [ 33 , 44 , 45 , 46 , 47 , 54 , 57 , 58 , 59 , 60 , 61 , 62 ] the p- or c-ANCA positivity was associated with Cocaine Induced Midline Destructive Lesions (CIMDL) ( n = 5) [ 44 , 57 ], vasculitis ( n = 8) [ 33 , 47 , 58 , 59 , 60 , 61 ], membranous glomerulonephritis ( n = 4) [ 58 , 62 ], pyoderma gangrenosum ( n = 1) [ 54 ], neutropenia complicated with bowel necrosis ( n = 1) [ 46 ], and cerebral white matter dysfunction ( n = 1) [ 45 ]. These autoimmune pathologies were more frequent in women (100% ANCA positivity) than men (90% of ANCA positivity) [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Less is known about cocaine’s effects on venous endothelial cells, although other cases of cocaine-induced pulmonary embolism exist [ 6 , 7 ]. It has been found that adulterants like levami-sole, which is present in 69% of cocaine samples, are known to cause pulmonary damage, including pulmonary fibrosis [ 10 – 12 ].…”
Section: Discussionmentioning
confidence: 99%